Effect of Dietary Supplementation of Echinacea purpurea on the Humoral Immune Response Against Newcastle Disease Vaccine in Broiler Chicks - Mayahi, Mansour; Abadshapory, Masghoud Reza Saify; Najafzadeh, Hossain; Kefayat , Marzieh (International Journal of Poultry Science, 2011)
In order to study evaluated effect of Echinacea purpurea on the humoral immune system against live vaccine of Newcastle disease, 120 day-old broiler chicks were divided randomly into 6 groups of 20 chicks each. Group 1, 2 chicks were kept as unvaccinated and vaccinated control chicks respectively and fed only basic diet. Group 3 and 4 chicks were fed basic diet supplement with 0.1 and 0.5% Echinacea purpurea respectively for 6 weeks. Group 5 and 6 chicks were fed basic diet supplemented with 0.1 and 0.5% Echinacea for first 2 weeks of age respectively. All group were vaccinated with live Newcastle (B strain) at 9 day of age by eye drop route. The antibody titer against Newcastle disease vaccine was measured by hemagglutination inhibition and ELISA tests. The result of present study showed that the Echinacea purpurea does not significantly increased specific antibody titer against vaccination with live Newcastle (B strain) vaccine. One time vaccination of birds with ND vaccine was not sufficient for protection of birds and revaccination is necessary. The correlation coefficient for ELISA and HI test was 91%.